HDL – associated proteins in hypertensive disorders of pregnancy - Ivanišević, Jasmina; Ardalić, Daniela; Zeljković, Aleksandra; Vekić, Jelena; Gojković, Tamara; Vladimirov, Sandra; Antonić, Tamara; Munjas, Jelena; Miković, Željko; Stefanović, Aleksandra (Biologia Serbica, 2023)
Hypertensive disorders of pregnancy are associated with various complications and long-term health risks for both mother and child. Preeclampsia, a form of hypertensive disorder, is characterized by gestational hypertension and proteinuria. It is a serious condition that can lead to maternal morbidity and fetal mortality, as well as increased risk of cardiovascular disease later in life. The role of high-density lipoproteins (HDL) in hypertensive disorders of pregnancy has also been investigated. HDL contains many different proteins and is known for its anti-atherogenic, anti-inflammatory, and anti-oxidant properties. Because of their beneficial vascular effects, HDL proteins may prevent vascular damage in physiological pregnancy. However, dysfunctional HDL may be associated with vascular damage and hypertension in pregnancy. Further research is needed to elucidate the HDL proteome and its role in these conditions.